An assessment of the biological and economic efficiency in conversion of milk to growth in N'Dama calves - Agyemang, K.; Clifford, K.; Little, D.A. (Cambridge University Press, 1993)
Two groups of light N'Dama calves were fed different quantities of milk from birth to 10 months of age to compare efficiencies fo converting milk to live-weight gain, and to assess the economic efficiencies of the two feeding regimes. Group one receives an average of 347 kg per calf, with a daily and seasonal pattern of feeding designed to stimulate a village production system where calves have access to only part of the milk produced by their dams, the rest being extracted from human consumptions. Group Two received an average of 617 kg per calf, and simulated situations where no milk is extracted such as in a ranch or station - type of operation. During the first 6 months, when growth was certainly mediated only by milk, and live-weight gains were consistently positive at 151 and 262 g/day in groups 1 and 2 respectively, the biological conversion of milk to live weight did not differ between groups (8.7 8.8 kg milk per kg live-weight gain). When the two groups were compared over the same weight range to remove possible effects of variable maintainance requirements, the conversion efficiencies again did not differ significantly. Over the whole 10-month period the biological conversion factors were slightly less favourable but still not different between groups (9.5 9.4 kg/kg). When monetary values of milk and live weight at formgate prices were applied to quantities of milk consumed and calf live-weight increases, the cost efficiency of group 1 was superior to that of group 2. Based on these findings and results from other on-farm experiments in The Gambia, it was concluded that the current practice of partial milk extraction as occurs in the village production system is a logical approach for profit maximization.